APP substrate ectodomain defines amyloid‐β peptide length by restraining γ‐secretase processivity and facilitating product release - Koch, Matthias; Enzlein, Thomas; Chen, Shu‐Yu; Petit, Dieter; Lismont, Sam; Zacharias, Martin; Hopf, Carsten; Chávez‐Gutiérrez, Lucía (The EMBO journal, 2023)
Sequential proteolysis of the amyloid precursor protein (APP) by γ‐secretases generates amyloid‐β (Aβ) peptides and defines the proportion of short‐to‐long Aβ peptides, which is tightly connected to Alzheimer's disease (AD) pathogenesis. Here, we study the mechanism that controls substrate processing by γ‐secretases and Aβ peptide length. We found that polar interactions established by the APPC99 ectodomain (ECD), involving but not limited to its juxtamembrane region, restrain both the extent and degree of γ‐secretases processive cleavage by destabilizing enzyme-substrate interactions. We show that increasing hydrophobicity, via mutation or ligand binding, at APPC99‐ECD attenuates substrate‐driven product release and rescues the effects of Alzheimer's disease‐associated pathogenic γ‐secretase and APP variants on Aβ length. In addition, our study reveals that APPC99‐ECD facilitates the paradoxical production of longer Aβs caused by some γ‐secretase inhibitors, which act as high‐affinity competitors of the substrate. These findings assign a pivotal role to the substrate ECD in the sequential proteolysis by γ‐secretases and suggest it as a sweet spot for the potential design of APP‐targeting compounds selectively promoting its processing by these enzymes.